2017
DOI: 10.14740/jocmr3067w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Switching From an Anti-Diabetic Loose Dose Combination to a Fixed Dose Combination Regimen at Equivalent Dosage for 6 Months on Glycemic Control in Japanese Patients With Type 2 Diabetes: A Pilot Study

Abstract: BackgroundPatients with type 2 diabetes mellitus often take multiple anti-diabetic drugs for a long period. Fixed dose combination (FDC) therapy is expected to improve drug adherence for patients with diabetes. The effect of switching from a loose dose combination (LDC) regimen to an FDC regimen at equivalent dosage on glycemic control has not been evaluated fully. Therefore, we investigated the effect of switching from LDC to FDC at equivalent dosage for 6 months on glycemic control in Japanese patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Combining antidiabetic agents with complementary mechanisms of action is fundamental to the management of diabetes 16 . While FDCs have only recently been launched in Japan, they offer a method of simplifying complex regimens, reducing treatment burden through less frequent dosing and allowing multiple medications with complementary mechanisms of actions to be given in a single formulation 22 . In addition, novel once weekly administration schedules also allow regimen simplification, which may help improve treatment adherence 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Combining antidiabetic agents with complementary mechanisms of action is fundamental to the management of diabetes 16 . While FDCs have only recently been launched in Japan, they offer a method of simplifying complex regimens, reducing treatment burden through less frequent dosing and allowing multiple medications with complementary mechanisms of actions to be given in a single formulation 22 . In addition, novel once weekly administration schedules also allow regimen simplification, which may help improve treatment adherence 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, it has been estimated that approximately 60% of patients with diabetes forget to take their medication at some stage 10. Non-adherence to antidiabetic medications is associated with increased healthcare expenditure and higher rates of hospitalisation and death 11 12. It has been suggested that use of a once-weekly DPP-4i or a fixed-dose combination (FDC) therapy may improve adherence in patients with T2DM 13.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that use of a once-weekly DPP-4i or a fixed-dose combination (FDC) therapy may improve adherence in patients with T2DM 13. A 10% increase in adherence has been linked with a 0.1% decrease in HbA1c 11 14. Recent studies suggest that dual-therapy schedules containing a DPP-4i may improve persistence relative to DPP-4i monotherapy,15 or SU-containing schedules 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation